PROTECTING ONLINE PRIVACY IN THE PRIVATE SECTOR: IS THERE A ‘BETTER’ MODEL? - Dubrovsky, David (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
“No human reads your mail to target ads or other information without your consent.” This is an excerpt included in Google’s Gmail Privacy Policy that explains the methodology underlying the interactive advertisement process incorporated into Google’s web-based e-mail service. Google’s inclusion of this assurance reveals a number of complex privacy concerns. As information technology continues to influence privacy on the Internet, the latter’s viability as a legally protected right comes into question. The theme of this essay competition is the relation between law and cyberspace. In addressing the struggle faced by governments and industry experts to identify effective approaches for regulating emerging technologies, the author compares the effectiveness of legislation and industry self regulation aimed at protecting online privacy. Three central issues are considered: consent, burden of protection and enforcement. The analysis suggests that neither course is mutually exclusive and that a consolidated approach provides a more effective level of protection and a more malleable framework to meet future needs.